Standardizing training protocol of an intestinal transplantation model: A learning curve study - Azpiroz, Josefina (2025)
Experimental: Rodent models of intestinal transplantation are crucial for advancing our understanding of various biological processes related to the procedure, including ischemia-reperfusion injury, acute cellular rejection and immunological tolerance, among others. These models also provide a platform for developing strategies and therapeutics aimed at improving long-term survival, with the ultimate goal of translating laboratory findings into clinical applications. With over twenty years of experience in intestinal transplantation in rodents, our team currently achieves a survival rate of 83 % in orthotopic transplants and 85 % in heterotopic transplants— success rates comparable to those reported by leading research groups in the field. This manuscript outlines the key steps involved in achieving successful results in rat intestinal transplantation models. It covers the entire process, from basic microsurgical training and graft procurement to implantation and postoperative care of the recipient. We hope this work will serve as a valuable guide for research groups seeking to establish these experimental transplantation models in their own laboratories.